Evaluation of Community-Based Education Programs - Irwan Desiharto; Dede Maulana Malik; Cecep Hilman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
From the beginning of the development of educational evaluation around the 1960s until now, evaluation figures have developed about dozens of evaluation models. These models are also based on the approach, forms and objectives of evaluation. These models are used to evaluate programs or activities in various aspects, be it in the fields of politics, economics, law, culture and education. Evaluation of educational programs is the process of description, data collection and submission of information to decision makers that will be used to consider whether the program needs to be improved, stopped or continued. The implementation of educational programs can be viewed from various points of view. These points of view include from the government as a policy maker, from the community as a user, from educators, for example in terms of program effectiveness. To determine the success of the educational program implemented, an evaluation is needed, called program evaluation. Because it specifically evaluates educational programs, it is often referred to as educational program evaluation. Program evaluation is a method to determine the performance of a program by comparing with predetermined criteria or goals to be achieved with the results achieved. The conclusion is how good the program we make is if there is no evaluation then the program, so an evaluation is needed whether the program is worth continuing or not